(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Reye’s syndrome is a rare but potentially fatal condition that predominantly affects children, characterized by acute encephalopathy and fatty liver degeneration. The pathophysiology remains incompletely understood, though associations with viral infections and aspirin use have been identified. This article reviews the current understanding of Reye’s syndrome, emphasizing its clinical presentation, diagnostic challenges, and advancements in treatment strategies. Early recognition and supportive care are critical for improving outcomes. The review also discusses preventive measures, including the avoidance of aspirin in pediatric populations during viral illnesses. Acute pediatric metabolic encephalopathy known as Reye’s syndrome presents with rapid progression of neurological impairment and hepatic lipid accumulation, necessitating urgent clinical intervention. Etiological factors include viral infections, particularly influenza and varicella, combined with exogenous triggers such as salicylate administration during febrile illnesses. Recent investigations emphasize the importance of timely recognition and implementation of comprehensive supportive care protocols encompassing metabolic stabilization, intracranial pressure management, and targeted monitoring of hepatic and cerebral function. Preventive strategies focusing on educational outreach and avoidance of contraindicated pharmacological agents demonstrate measurable reductions in incidence. Contemporary research underscores the integration of molecular biomarkers, advanced imaging modalities, and electrophysiological assessment to refine early diagnostic capabilities. Emphasis on multidisciplinary collaboration and individualized therapeutic planning facilitates optimization of functional recovery and minimizes the risk of persistent neurological deficits. The review consolidates current knowledge regarding pathophysiology, clinical staging, laboratory evaluation, and evidence-based management approaches, highlighting the critical role of prevention and early intervention in pediatric populations.